Battleships - Marriott, Leo (Igloo Books, 2010)
Battleships dominated the seas from their inception in the 18th century through to the first half of the 20th century and were a symbol of a contry's military strength and power. Including detailed specifications, appendices, a glossory, bibliography and index, this book gives clear insight into the development, construction, operation and engagement of these fighting machines. Complete with stunning photography and detailed texts that place each era of battleship in its political context. This book is the ultimate guide to battleships and battlecruisers, taking you from the pre-dreadnaought are through the two world wars, Pearl Harbour and beyond.